Association of diet quality and quantity with the risk of sarcopenia based on the Chinese diet balance index 2022 - Yu, Xiao; Zhang, Mei; Wang, Yongjun; Yu, Lianlong; Zhao, Changsheng (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to analyze the dietary structure characteristics and the association between food intake and sarcopenia among older adults in China, based on the DBI-22 scoring criteria. This analysis was intended to provide guidance for improving dietary balances and nutritional management related to sarcopenia.MethodsA stratified random cluster sampling method was employed to select 1,478 elderly individuals aged 60 and above in Chinese. A questionnaire survey was conducted, which included the Sarcopenia-Five (SARF) scale and Food Frequency Questionnaires (FFQ). The China Dietary Balance Index 2022 (DBI-22) was utilized to assess dietary quality. Generalize Linear Model (GLM) and logistic regression analysis were applied to examine dietary factors influencing sarcopenia.ResultsThe issue of dietary imbalance among the elderly was found to be severe, with 52.11% of participants exhibiting deficient intake, 46.54% displaying excessive intake, and 59.78% demonstrating overall dietary imbalance (moderate-to-high levels). Screening conducted using the SARF scale revealed a sarcopenia rate of 24.82%. Excessive intake of cereal was identified as a risk factor for sarcopenia (OR = 1.490, 95%CI: 1.149, 1.939; p = 0.003), whereas increased consumption of red meat and products, poultry and game was found to reduce this risk (OR = 0.560, 95%CI: 0.342, 0.886; p = 0.016).ConclusionThe dietary habits of older adults were problematic, with both insufficient and excessive food intake. Too much cereal posed a risk for sarcopenia, whereas more red meat and products, poultry and game served as a protective factor.